2015
DOI: 10.1128/aem.00212-15
|View full text |Cite
|
Sign up to set email alerts
|

Nisin H Is a New Nisin Variant Produced by the Gut-Derived Strain Streptococcus hyointestinalis DPC6484

Abstract: dAccumulating evidence suggests that bacteriocin production represents a probiotic trait for intestinal strains to promote dominance, fight infection, and even signal the immune system. In this respect, in a previous study, we isolated from the porcine intestine a strain of Streptococcus hyointestinalis DPC6484 that displays antimicrobial activity against a wide range of Grampositive bacteria and produces a bacteriocin with a mass of 3,453 Da. Interestingly, the strain was also found to be immune to a nisin-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 48 publications
1
74
3
Order By: Relevance
“…Differences in nisin cluster gene arrangements have been described before [12,19,51] and have been proposed to be a consequence of horizontal gene transfer, but up to now only nisin H has been found to be different in its gene content, with the absence of a detectable nisI [12]. At the prepeptide level, the nsoA genes deviated from the conserved leader peptide and cleavage sequences found in other nisA genes.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Differences in nisin cluster gene arrangements have been described before [12,19,51] and have been proposed to be a consequence of horizontal gene transfer, but up to now only nisin H has been found to be different in its gene content, with the absence of a detectable nisI [12]. At the prepeptide level, the nsoA genes deviated from the conserved leader peptide and cleavage sequences found in other nisA genes.…”
Section: Discussionmentioning
confidence: 90%
“…However, it was interesting to note that the native producer B. obeum showed sensitivity to nisin A, suggesting that the immunity system may require induction. O'Connor et al [12] also found that the native nisin U-producing strain S. uberis was inhibited by supernatant from a nisin A producer.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The bacteriocins are designated nisin A, nisin Z, nisin Q, F nisin (Lactococcus lactis), and nisin U (Streptococcus uberis) [2][3][4][5][6]. Recently, nisin H variant produced by Streptococcus hyointestinalis was described by O'Connor et al [7].…”
Section: Introductionmentioning
confidence: 99%